Preparation and Photocatalytic Activity of CdSe-TiO2 Composite Designed for High Decomposition Effect - Chen, Ming-Liang; Peng, Mei-Mei; Jang, Hyun-Tae; Oh, Won-Chun (Asian Journal of Chemistry, 2011)
In this study, CdSe-TiO2 composite were synthesized by a facile sol-gel method and characterized by nitrogen adsorption isotherms (77 K), X-ray diffraction, scanning electron microscopy with energy dispersive X-ray (EDX) analysis and UV-visible diffuse reflectance spectrophotometer. The photocatalytic activity was investigated by degrading methylene blue, methyl orange and rhodamine B (Rh.B) in aqueous solution under irradiation of UV light as well as visible light. The absorbance of degraded methylene blue solution was determined by UV-visible spectrophotometer. The results revealed that the CdSe-TiO2 composite exhibited much higher photocatalytic activity than pure TiO2 both under irradiation of UV light as well as visible light for photodegradation of methylene blue solution.